Perceived Academic Competence Among Arab Open University Students (Sultanate of Oman) - Al-Ghafri, Hamed Hamood; Al-shabibi, Amal Saleem Mohammed; Al-ajmi, Laila Khamis Ali; Bani Uraba, Lamya Yousuf Nasser (Journal of Educational and Psychological Sciences, 2020)
The research aimed to identify the level of perceived academic competence among Arab Open University students (Sultanate of Oman) and to identify the extent of the difference of the perceived level of academic competence according to the variables of specialization (Information Technology and Business Administration) and academic level (freshman and sophomore) and the interface between them.The research used the descriptive method and the Perceived Academic Competence scale to achieve the goals of the study and answer its questions, an indicator related to the extent of students' perception and awareness of their ability to achieve academic success. It consists of (9) scales applied to an intentional sample of (94) male and female students of AOU.The research has concluded that the general average of the perceived academic competence of the Arab Open University students in Business Administration and Information Technology for the first and second year amounted to (3.85) and this indicates that the study sample has a high degree of perceived academic competence.There were no statistically significant differences in the level of perceived academic competence according to the variables of specialization and academic year level. The results also indicated that there is no interface between the specialization and the academic year level. Rendering to the results, several recommendations and proposals were presented to improve the academic competence of university students and the general undergraduate students in the Sultanate of Oman and the Arab countries.
Keywords: perceived academic proficiency; Arab Open University students; Sultanate of Oman